Can the European Court of Human Rights shape European public order? - Dzehtsiarou, Kanstantsin ca. 20./21. Jh (Cambridge University Press, 2022)
In this book, Kanstantsin Dzehtsiarou argues that, from the legal perspective, the formula 'European public order' is excessively vague and does not have an identifiable meaning; therefore, it should not be used by the European Court of Human Rights (ECtHR) in its reasoning. However, European public order can also be understood as an analytical concept which does not require a clearly defined content. In this sense, the ECtHR can impact European public order but cannot strategically shape it. The Court's impact is a by-product of individual cases which create a feedback loop with the contracting states. European public order is influenced as a result of interaction between the Court and the contracting parties. This book uses a wide range of sources and evidence to substantiate its core arguments: from a comprehensive analysis of the Court's case law to research interviews with the judges of the ECtHR.
Title from publisher's bibliographic system (viewed on 25 Nov 2021)
Keywords: European Court of Human Rights; Human rights / Europe